Teks Mitos Tirta Selaka di Pura Kereban Langit Desa Sading Kecamatan Mengwi: Analisis Struktur dan Fungsi - Surya Dewi Indah Sari, Ni Kadek; Mulyawati, Tjok Istri Agung; Ngurah Sulibra, I Ketut (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p35, 2018)
This analysis aims to reveal the structure and express the function contained in the text of the myth of Tirta Selaka in the Kereban Langit Temple. In this research used structural theory and functional theory. Methods and techniques used in this study are divided into three stages: (1) Methods and techniques of data provisioning using observation methods and interview techniques assisted by purposive sampling techniques, recording techniques, recording techniques and translation techniques. (2) Methods and techniques of data analysis using qualitative methods and descriptive analytic techniques. (3) Methods and techniques of presentation of data results using informal methods supported by deductive and inductive techniques. The results obtained from this study, namely narrative structure include: nine incidents, using a straight groove and the groove is divided into five stages, situations (penyituasian), generating circumstances (incidence of conflict), Rising Action (increased conflict), Climax (climax), denoument (problem solving). The characters are divided into two, namely the main character and the secondary figure. The theme that built the text of the myth of Tirta Selaka is a magical theme. Background is divided into three, ie background place, background, and social background. In addition, this research reveals the functions contained in the text of the myth of Tirta Selaka in the Kereban Langit Temple, including: religious functions, educational functions, magical functions, and as a means of legalization of institutions and cultural institutions.